1989
DOI: 10.1002/j.1460-2075.1989.tb08517.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutations in heat-shock genes groES and groEL on protein export in Escherichia coli.

Abstract: Escherichia coli heat‐shock proteins GroES and GroEL are essential cytoplasmic proteins, which have been termed ‘chaperonins’ because of their ability to assist protein assembly of bacteriophage capsids and multimeric enzymes of foreign origin. In this report we show that temperature‐sensitive mutations in groES and groEL genes cause defective export of the plasmid‐encoded beta‐lactamase (Bla) in vivo. Since efficient translocation of proteins across biological membranes is thought to be supported by cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(154 citation statements)
references
References 43 publications
2
151
0
1
Order By: Relevance
“…It is possible that heat shock proteins recognize and bind to partially folded intermediates, forming a tight complex that does not dissociate and is eventually sequestered within an aggregate. GroEL, a cytoplasmic chaperonin, has been shown to be necessary for the secretion of 0-lactamase (Kusukawa et al, 1989). It has also been shown to interact with the 8-lactamase precursor in uitro (Laminet et al, 1990 the major E. coli chaperonins (GroEL/ES and DnaK) nor the lower molecular weight heat shock proteins discovered by Allen et al (1992) were found in the cytoplasmic inclusion bodies formed by A(-2O-l)-~-lactamase, indicating that such proteins are not necessarily involved in protein aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that heat shock proteins recognize and bind to partially folded intermediates, forming a tight complex that does not dissociate and is eventually sequestered within an aggregate. GroEL, a cytoplasmic chaperonin, has been shown to be necessary for the secretion of 0-lactamase (Kusukawa et al, 1989). It has also been shown to interact with the 8-lactamase precursor in uitro (Laminet et al, 1990 the major E. coli chaperonins (GroEL/ES and DnaK) nor the lower molecular weight heat shock proteins discovered by Allen et al (1992) were found in the cytoplasmic inclusion bodies formed by A(-2O-l)-~-lactamase, indicating that such proteins are not necessarily involved in protein aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no interaction of GroEL was seen with soluble cytoplasmic proteins or with mature secreted proteins. However, the significance of these in vitro experiments is not entirely clear: in temperature-sensitive GroEL and GroES mutants only the processing of ^-lactamase was slowed down; there was no effect on the secretion of other proteins, including proOmpA (KUSUKAWA et al 1989). …”
Section: Translocation Of Proteins Across Membranesmentioning
confidence: 99%
“…Only in the presence of GroEL was the export competence of newly synthesized ^-lactamase conserved during preincubation. Therefore, the GroEL protein was proposed to stabilize a secretion-competent conformation and exert a chaperone function analogous to SecB and trigger factor (BOCHKAREVAet al 1988;KUSUKAWA et al 1989). As shown recently, the overproduction of GroEL in E. coli facilitates the export of a hybrid protein consisting of the signal sequence and the amino terminal region of the maltose-binding protein fused to /?-galactosidase (PHILLIPS and SILHAVY 1990).…”
Section: Translocation Of Proteins Across Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…While in the E. coli cell only the precursor may interact with GroEL before it is transported to the periplasm [8,9], this model system offers unique insight into chaperone guidance of protein folding because of differences in interaction between GroEL and various forms of ß-lase. The precursor of ß-lase is known to bind very tightly [10], while the mature form binds much more weakly [7], and differences between reduced and oxidized ß-lase are also apparent (this study).…”
Section: Introductionmentioning
confidence: 99%